Neuroendocrine carcinoma of ovary: Hitherto rare entity in primary ovarian tumors - Md A Osama; Seema Rao; Punita Bhardwaj; Geeta Mediratta; Sunita Bhalla; Sonia Badwal (Wolters Kluwer Medknow Publications, 2023)
Neuroendocrine neoplasms (NEN) of the female genital tract are extremely uncommon. These tumors can be broadly divided into well differentiated (carcinoid) and poorly differentiated NEN (small cell and large cell carcinomas). Occurrence of neuroendocrine carcinomas (NECs) in ovary has rarely been reported. These high-grade malignant tumors have a fulminant clinical course with a short period of survival, even when diagnosed at an early stage. We hereby report two cases of primary neuroendocrine carcinoma of the ovary.